Negotiating weights for burden sharing rules among heterogeneous parties: Empirical evidence from a survey among delegates in international climate negotiations - Martin Kesternich; Andreas Löschel; Andreas Ziegler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Given the vital and controversial debate on fairness concerns in international climate negotiations, the acceptance of a climate treaty may be fostered if the distribution of costs and benefits from global environmental protection is perceived to be fair. Since an agreement must be acceptable to all negotiating countries, it is likely that no single burden sharing concept will gain unconditional support from all parties. We have conducted a world-wide survey among participants in international climate negotiations to address the question whether negotiating weights for different fairness concepts may enlarge the bargaining space among heterogeneous agents and overcome the currently dominating self-interested use of fairness claims. Even though our empirical results confirm different positions on burden sharing among key regions, there is evidence that a broad majority favors allocations that are based on a variety of fairness rules. Turning the debate rather towards justice claims based on needs than towards culpability may serve as a fruitful starting point to depart from a purely egoistic use of equity rules in international climate negotiations.
urn:nbn:de:bsz:180-madoc-368597
Keywords: D63; H41; Q54; 330; international climate negotiations; distributive justice; equity preferences; burden sharing rules